Překryvný syndrom SLE - ANCA asociovaná vaskulitida - Skácelová, Martina; Horák, Pavel; Janková, Jana (Vnitrni lekarstvi, 2021)
Incidence of ANCA antibodies in patients with systemic lupus erythematosus (SLE) is described in 24-31 %, but they are not related to the distribution and severity of organ involvement in SLE; the routine monitoring is not recommended. Overlap syndrome of systemic lupus erythematosus and ANCA associated vasculitis (AAV) is rare. The difficult diagnosis and treatment of this syndrome is described in this case report of the patient with SLE and severe kidney involvement resulting from AAV.
Keywords: ANCA associated vasculitis; overlap syndrome; systemic lupus erythematosus.; systémový lupus erythematodes; ANCA-asociované vaskulitidy; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Humans; Lupus Erythematosus, Systemic; Syndrome; syndrom; lidé; incidence; Incidence